Wits Architecture Student Works 1922-1980; Boers, SD (1970) - Boers, S D (My University, 2014)
Design: House, elevations; Boers, SD (architecture student) 1970. Wits Student Works. University of the Witwatersrand, Johannesburg, South Africa.
Design: House, elevations; Boers, SD (architecture student) 1970. Wits Student Works. University of the Witwatersrand, Johannesburg, South Africa.
Keywords: Boers, S D; House, elevations; Wits Architecture Students Works 1922-1980